Pieter Hugo : this must be the place - Hugo, Pieter; Demos, T. J.; Schuman, Aaron; Fotomuseum Den Haag.; Musée de l'Elysée (Lausanne, Switzerland) (Munich ; New York : Prestel, 2012)
Pieter Hugo has been documenting his native continent of Africa since his late teens. This retrospective volume collects photographs from each of his earlier series, as well as portraits and landscapes that have never been shown or published before--
Catalog of an exhibition held at The Hague Museum of Photography, the Hague, Mar. 3-May 20, 2012 and Musée de l'Elysée, Lausanne, June 9-Sept. 2, 2012.
Includes bibliographical references.
boek
Keywords: Hugo, Pieter; Hugo, Pieter